2012
DOI: 10.1186/1471-2407-12-450
|View full text |Cite
|
Sign up to set email alerts
|

Novel anti-HER2 monoclonal antibodies: synergy and antagonism with tumor necrosis factor-α

Abstract: BackgroundOne-third of breast cancers display amplifications of the ERBB2 gene encoding the HER2 kinase receptor. Trastuzumab, a humanized antibody directed against an epitope on subdomain IV of the extracellular domain of HER2 is used for therapy of HER2-overexpressing mammary tumors. However, many tumors are either natively resistant or acquire resistance against Trastuzumab. Antibodies directed to different epitopes on the extracellular domain of HER2 are promising candidates for replacement or combinatoria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 43 publications
0
22
0
Order By: Relevance
“…It was recently shown that targeting transmembrane TNF-α was effective in delaying tumor growth and inhibiting tumor metastasis (Yu M. et al, 2013). TNF-α inhibition may synergize with anti-HER2 therapy to improve treatment outcomes (Ceran et al, 2012). These studies suggest that TNF-α may play a significant role in breast tumor progression not only by directly acting on breast cancer cells, but also by recruiting and activating suppressive immune cells.…”
Section: Proinflammatory Cytokines and Chemokinesmentioning
confidence: 99%
“…It was recently shown that targeting transmembrane TNF-α was effective in delaying tumor growth and inhibiting tumor metastasis (Yu M. et al, 2013). TNF-α inhibition may synergize with anti-HER2 therapy to improve treatment outcomes (Ceran et al, 2012). These studies suggest that TNF-α may play a significant role in breast tumor progression not only by directly acting on breast cancer cells, but also by recruiting and activating suppressive immune cells.…”
Section: Proinflammatory Cytokines and Chemokinesmentioning
confidence: 99%
“…Human epidermal growth factor receptor (HER) family consists of four different high affinity tyrosine kinase receptors including EGFR (HER 1 or ErbB-1), HER2/c-neu (ErbB-2), Her 3 (ErbB-3), and Her 4 (ErbB-4) [1,2]. The HER2 over-expression, as a part of neoplastic progression, has been implicated in tumor proliferation, division, and angiogenesis [3].…”
Section: Introductionmentioning
confidence: 99%
“…In the absence of a known ligand, hetero-dimerization of this receptor with other family members, particularly with EGFR which results in effective activation of intracellular signaling pathways, promotes cell proliferation and survival [3][4][5]. Since these cell surface receptors (HER2 and EGFR) are amplified and over-expressed in a large number of tumor types, they are considered as ideal targets for selective molecular therapy of cancer [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations